Genetic and Epigenetic Approaches for the Possible Detection of Adulteration and Auto-Adulteration in Saffron (Crocus sativus L.) Spice - Soffritti, Giovanna; Busconi, Matteo; Sánchez, Rosa; Thiercelin, Jean-Marie; Polissiou, Moschos; Roldán, Marta; Fernández, José (Molecules (Basel, Switzerland), 2016)
Saffron (Crocus sativus L.) is very expensive and, because of this, often subject to adulteration. Modern genetic fingerprinting techniques are an alternative low cost technology to the existing chemical techniques, which are used to control the purity of food products. Buddleja officinalis Maxim, Gardenia jasminoides Ellis, Curcuma longa L., Carthamus tinctorius L. and Calendula officinalis L. are among the most frequently-used adulterants in saffron spice. Three commercial kits were compared concerning the ability to recover PCR-grade DNA from saffron, truly adulterated samples and possible adulterants, with a clear difference among them, mainly with the processed samples. Only one of the three kits was able to obtain amplifiable DNA from almost all of the samples, with the exception of extracts. On the recovered DNA, new markers were developed based on the sequence of the plastid genes matK and rbcL. These primers, mainly those developed on matK, were able to recognize saffron and the adulterant species and also in mixtures with very low percentages of adulterant. Finally, considering that the addition of different parts of saffron flowers is one of the most widespread adulterations, by analyzing the DNA of the different parts of the flower (styles, stamens and tepals) at the genetic and epigenetic level, we succeeded in finding differences between the three tissues that can be further evaluated for a possible detection of the kind of fraud.